Evaluation of springtime deworming strategies for beef cow/calf pairs - Pfeifer, M.L.; Baker, J.C.; Seeger, J.T.; Blasi, Dale A.; Newdigger, Glenn E., Jr. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A field study was conducted at three different locations in south central Kansas to determine the effects of Dectomax® (DECTO) or Ivomec PO® (IVO) compared to no treatment (CONT) on the liveweight gain and reproductive performance of beef cow/calf pairs. Across all three locations, no differences occurred among treatments in cow and calf live weight gain, cow body condition, pregnancy rate, or age of fetus (P>.05). Low egg counts suggest that the parasite load was too low for a response to parasite control.
Keywords: Beef; Spring deworming; Cow/calf pairs